2023
DOI: 10.1101/2023.10.19.563125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trait Reward Sensitivity Modulates Connectivity with the Temporoparietal Junction and Anterior Insula during Strategic Decision Making

Daniel Sazhin,
James B. Wyngaarden,
Jeff B. Dennison
et al.

Abstract: Many decisions happen in social contexts such as negotiations, yet little is understood about how people balance fairness versus selfishness. Past investigations found that activation in brain areas involved in executive function and reward processing was associated with people offering less with no threat of rejection from their partner, compared to offering more when there was a threat of rejection. However, it remains unclear how trait reward sensitivity may modulate activation and connectivity patterns in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 112 publications
(211 reference statements)
1
2
0
Order By: Relevance
“…71 The anterior insula may also be important in social decision making, with fMRI activation in this structure associated with strategic decisions that maximize personal gain and minimize chance of rejection by a partner in social settings. 72 Supporting the findings of these prior studies, we identify neurophysiological signals within the OFC, amygdala, and insula that are associated with decisions that maximize gain and minimize loss, suggesting a role for these regions in reward and punishment based decision making.…”
Section: Discussionsupporting
confidence: 83%
“…71 The anterior insula may also be important in social decision making, with fMRI activation in this structure associated with strategic decisions that maximize personal gain and minimize chance of rejection by a partner in social settings. 72 Supporting the findings of these prior studies, we identify neurophysiological signals within the OFC, amygdala, and insula that are associated with decisions that maximize gain and minimize loss, suggesting a role for these regions in reward and punishment based decision making.…”
Section: Discussionsupporting
confidence: 83%
“…If a parKcipant missed a trial, the screen indicated they were too slow and logged a missed trial. [8].…”
Section: Experimental Tasksmentioning
confidence: 99%
“…The overarching goal of this project was to characterize the associaKons between neural responses to social and non-social rewards, trait reward sensiKvity, substance use, and other psychosocial variables [5]. To date, we have published/preprinted efforts that show links between substance use and trait reward sensiKvity in tasks focused on social reward [6], social context [7], and social decision making [8]. The current data arKcle adds to these papers/preprints by describing the full scope of the dataset and outlining possibiliKes for reuse.…”
Section: Introductionmentioning
confidence: 99%